“PSIKOLOGISENI” SENIMAN ANTARA PERSEPSI, FANTASI DAN EMOSI - Juni Amanullah; Fivin Bagus Septiya Pambudi (SULUH: Jurnal Seni Desain Budaya, 2021)
In the science of human psychology is a creature that has a soul and in a life that has a soul that is reflected in human behavior and activities in their daily lives. Beauty or aesthetics is something that is related to something beautiful and a special taste in enjoying it. In art life when an artist feels a lot of what is inside him, the results will be divested into a work of art. From the two disciplines of science between psychology and art, the writer uses psychological methods, namely perception, fantasy, feeling and emotion to dissect in the life of art with a subject, namely artists. Perception in the world of art by artists is the act of compiling, recognizing, and interpreting sensory information in order to provide a picture and understanding of the environment in the world of art. Artist's fantasy is something that is related to imagination or something that only exists in the mind or mind to be poured into a work of art. Artist's emotion is a feeling (intense / frequent) aimed at something more physical, that is, a work of art, the artist's emotions are expressed as a reaction to the results of an artist's perceptions and fantasies.